Pengaruh Perceived Organizational Support, Person-Job Fit, Dan Meaningfullness Of Work Terhadap Turnover Intention Yang Dimediasi Oleh Work Engagement Pada Karyawan House Keeping Di Co-Living Jakarta Barat - Asti Fatimah; Marisela Bethabara; Netania Emilisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
Employees are one of the essential elements and assets within an organization or company. The presence of Turnover Intention among employees certainly has a negative impact on the company's image and performance. This study was conducted on housekeeping employees in co-living spaces in West Jakarta, who potentially have a high Turnover Intention due to the lack of career clarity in their current jobs. The aim of this research is to analyze the Perceived Organizational Support, Person-job Fit, Meaningfulness of Work, Work Engagement, and Turnover Intention among housekeeping employees in co-living spaces in West Jakarta. The sample used in this study consisted of 260 housekeeping employees in co-living spaces in West Jakarta. The testing was conducted using Structural Equation Model (SEM) in the AMOS software, with data collection procedures involving questionnaires and literature review. The results of this study indicate that employees feel a lack of Perceived Organizational Support, Person-job Fit, Meaningfulness of Work, and Work Engagement in their jobs, which leads to the presence of Turnover Intention among employees. There is a significant positive influence between Perceived Organizational Support and Person-job Fit on Work Engagement. There is also a significant negative influence between Perceived Organizational Support and Turnover Intention, which is mediated by Work Engagement. Therefore, companies need to provide clear career development paths for employees to reduce the level of Turnover Intention.